2012
DOI: 10.1155/2012/356487
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Glucolipotoxicity-Induced Endoplasmic Reticulum Stress by a “Chemical Chaperone” in Human THP-1 Monocytes

Abstract: Chronic ER stress is emerging as a trigger that imbalances a number of systemic and arterial-wall factors and promote atherosclerosis. Macrophage apoptosis within advanced atherosclerotic lesions is also known to increase the risk of atherothrombotic disease. We hypothesize that glucolipotoxicity might mediate monocyte activation and apoptosis through ER stress. Therefore, the aims of this study are (a) to investigate whether glucolipotoxicity could impose ER stress and apoptosis in THP-1 human monocytes and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 56 publications
6
20
1
Order By: Relevance
“…In our present study, we proved that ox-LDL-induced upregulation of CHOP and apoptosis in macrophages could be prevented when PBA inhibited ER stress. This finding agrees well with that of a previous study 4142) .…”
Section: Discussionsupporting
confidence: 94%
“…In our present study, we proved that ox-LDL-induced upregulation of CHOP and apoptosis in macrophages could be prevented when PBA inhibited ER stress. This finding agrees well with that of a previous study 4142) .…”
Section: Discussionsupporting
confidence: 94%
“…ROS generation during glucose deprivation can result in cell death (Gao et al, 2012; Lenin et al, 2012; Malhotra et al, 2008). AMPK can be induced by glucose deprivation and mitochondrial O 2 − production (Wu and Wei, 2012) (Mackenzie et al, 2013) to reduce total ROS via the promotion of pentose phosphate shunt-mediated NADPH production (Jeon et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A potential mechanism by which monocyte-derived ROS is increased in T2D is ER stress (Lenin et al , 2012). While initially a compensatory attempt to maintain cellular homeostasis, sustained ER stress and activation of the unfolded protein response (UPR) is now thought to be the basis of a number of chronic diseases of both metabolic and cardiovascular nature (Eizirik et al , 2008; Hotamisligil, 2010a; Hotamisligil, 2010b; Hummasti & Hotamisligil, 2010; Gregor & Hotamisligil, 2011; Flamment et al , 2012; Fu et al , 2012; Cao & Kaufman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia, hyperinsulinemia, and hyperlipidemia are known triggers of ER stress in various tissues and cell types (Wang et al , 2005; Jeffrey et al , 2008; Komura et al , 2010; McAlpine et al , 2010; Mozzini et al , 2015; Rajan et al , 2016; Tampakakis et al , 2016). For instance, it has been shown that exposure of human monocytes to serum free medium with high levels of glucose plus palmitic acid, a mixture intended to emulate the circulating glucolipotoxic environment of T2D, resulted in the induction of ER stress markers and ROS production (Lenin et al , 2012). …”
Section: Introductionmentioning
confidence: 99%